1993
DOI: 10.1038/npp.1993.36
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Alterations in Electroencephalographic Activity in Adult Males

Abstract: The present investigation examined the effects of placebo (P), low-dose (LD), and high-dose (HD) ethanol on electroencephalographic (EEG) activity in 21 healthy, adult males (X = 22.7 years). Only one condition (P, W, or HD) was presented per day and the condition order was randomized. For each subject, blood-alcohol levels measured via breathalyzer and EEG activity, using the entire 10120 International System, were recorded both prior to and at intervals of 35, 70, 105, and 140 minutes after P, LD, or HD admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
3
19
0
2
Order By: Relevance
“…On the other hand there were no significant differences in the alcohol and placebo conditions for alpha 2. Ehlers et al (1989) and Cohen et al (1993) found similar results, though they only investigated cortical activity in the descending phase. Since alcohol only affected the slower alpha band, this could be interpreted as an alcohol induced shift of power from faster to slower frequencies and that participants are more likely therefore, to be drowsy during the alcohol sessions (Ehlers et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…On the other hand there were no significant differences in the alcohol and placebo conditions for alpha 2. Ehlers et al (1989) and Cohen et al (1993) found similar results, though they only investigated cortical activity in the descending phase. Since alcohol only affected the slower alpha band, this could be interpreted as an alcohol induced shift of power from faster to slower frequencies and that participants are more likely therefore, to be drowsy during the alcohol sessions (Ehlers et al, 1989).…”
Section: Discussionmentioning
confidence: 62%
“…It was also interesting that EEG changes in this current study found significant and more prominent increases in alpha 1 activity in the frontal regions compared to the central and posterior regions. Similarly, Cohen et al (1993) 14 found increases in the slow alpha activity band in the F3, F4, C3, and C4 sites. However, they began recording after 35 minutes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Cohen et al 10 examined the effects of placebo and low and high doses of alcohol on EEG activity in 21 healthy males and found that alcohol had significant effects on EEG activity at frontal and central montages. These authors suggested that differential responsiveness of both cortical regions and EEG frequency band exists related to the effects of alcohol.…”
Section: Discussionmentioning
confidence: 99%